SYNTHESIS OF NOVEL N-SUBSTITUTED AMPHIONIC MELAMINES WITH THE TANDEM 4-(1-CARBOXY-n-ALKOXY)PHENYL / 4-(n-OCTYLOXY)PHENYL UNITS AS POTENTIAL DENDRITIC BUILDING-BLOCKS - IONESCU-ZINCA, Stefania; LAMEIRAS, Pedro; PORUMB, Dan; GÁL, Emese; DARABANTU, Mircea (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Starting from etheric type derivatives of 4-aminophenol, namely (4-aminophenoxy)acetic acid or 4-(4-aminophenoxy)butyric acid and 4-(n-octyloxy)aniline, we report herein two routes of access to two novel N-substituted amphionic melamines with the tandem 4-(1-carboxy-n-alkoxy) phenyl/4-(n-octyloxy)phenyl units against the piperazin-1-yl group, as a basic site. The successful SN2-Ar aminations of cyanuric chloride performed with these amine-nucleophiles are discussed in terms of chemoselectivity, mainly in the third step of the synthesis, implying piperazine as such or its N-Boc-mono-protected form. The amphionic nature of the targeted melamines was fully confirmed both in solution (VT-NMR) and in the solid state (IR).